2024
DOI: 10.3389/fspor.2024.1296189
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual cycles and the impact upon performance in elite British track and field athletes: a longitudinal study

Benjamin P. Jones,
Ariadne L'Heveder,
Charlotte Bishop
et al.

Abstract: ObjectiveTo assess the prevalence of menstrual disorders and the perceived effect of menstrual cycles upon performance in elite athletes.MethodologyA longitudinal survey in the form of a questionnaire was sent to female track and field athletes at British Athletics every 6 months, over a five-year period between 1st October 2014 and 1st October 2019 in the United Kingdom (UK).Results128 athletes completed an average of 4.2 ± 2.9 questionnaires across the study period. The mean age of menarche was 14.2 ± 1.4 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Menarche leads to diverse hormonal changes and in turn changes in body composition including increased fat deposition [ 8 ] while also affecting the psychological and cognitive development of girls necessary for coping with adulthood [ 8 ]. Furthermore, the onset of the menstrual cycles has various negative influence on girls’ PA and sport participation before and during the menstrual cycle [ 9 ]. In this regard, Jones and co-workers reported that girls indicated negative cyclical symptoms affecting their PA and sport participation, such as bloating, lower-back- and pelvic pain, sleep disturbances, headaches and clumsiness before and during their menstrual cycles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menarche leads to diverse hormonal changes and in turn changes in body composition including increased fat deposition [ 8 ] while also affecting the psychological and cognitive development of girls necessary for coping with adulthood [ 8 ]. Furthermore, the onset of the menstrual cycles has various negative influence on girls’ PA and sport participation before and during the menstrual cycle [ 9 ]. In this regard, Jones and co-workers reported that girls indicated negative cyclical symptoms affecting their PA and sport participation, such as bloating, lower-back- and pelvic pain, sleep disturbances, headaches and clumsiness before and during their menstrual cycles.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Jones and co-workers reported that girls indicated negative cyclical symptoms affecting their PA and sport participation, such as bloating, lower-back- and pelvic pain, sleep disturbances, headaches and clumsiness before and during their menstrual cycles. The performance of more than 50% of power-, endurance- and throwing athletes were affected negatively during the menstrual cycle [ 9 ]. In this regard, differences in biological maturation before menarche, but also because of menarche, result in growth differences and more specifically weight-related changes that in turn will affect other aspects of life such as motor- and physical skill performance [ 10 , 11 ], which again can influence their PA levels in the future.…”
Section: Introductionmentioning
confidence: 99%